Genetics of medullary thyroid cancer: An overview. (May 2017) - Accardo, Giacomo; Conzo, Giovanni; Esposito, Daniela; Gambardella, Claudio; Mazzella, Marco; Castaldo, Filomena; Di Donna, Carlo; Polistena, Andrea; Avenia, Nicola; Colantuoni, Vittorio; Giugliano, Dario; Pasquali, Daniela
Abstract: Medullary thyroid carcinoma (MTC) represents 3–5% of thyroid cancers. 75% is sporadic and 25% is the dominant component of the hereditary multiple endocrine neoplasia (MEN) type 2 syndromes. Three different subtypes of MEN2, such as MEN2A, MEN2B, and Familial MTC (FMTC) have been defined, based on presence or absence of hyperparathyroidism, pheocromocytoma and characteristic clinical features. Mutations of the RET proto-oncogene are implicated in the pathogenesis of MTC, but there are many other mutational patterns involved. In MEN2A, Codon 634 in exon 11 (Cys634Arg), corresponding to a cysteine in the extracellular cysteine-rich domain, is the most commonly altered codon. Many other mutations include codons 611, 618, 620. In the genetical testing of RET mutations in MTCs, Next-Generation Sequencing (NGS) is taking an increasingly important role. One of the most important benefit is the comprehensive analysis of molecular alterations in MTC, which allows rapidly to select patients with different risk levels. There is a difference in miRNA expression pathway between sporadic and hereditary MTCs. Among sporadic cases, expression of miR-127 was significantly lower in those who harbor somatic RET mutations than those with wild-type RET. CDKN1B mutations are associated with many clinical pictures of cancers, such as MEN4. V109G polymorphism is associated with sporadic MTCs negative for RET mutations, and might influence the clinical course of the patients affected by MTC. Although surgery (i.e. total thyroidectomy with neck lymph node dissection) is the elective treatment for MTCs, about 80% of patients have distant metastases at diagnosis and in this cases surgery is not enough and an additional treatment is needed. Interesting results come from two large phase III clinical trials with two targeted tyrosine kinase inhibitors (TKIs), vandetanib and cabozantinib. Conclusions: New genetical testings and therapeutical approaches open new perspectives in MTC management. Highlights: Medullary thyroid carcinoma (MTC) represents 3–5% of thyroid cancers. 75% is sporadic and 25% is the dominant component of the hereditary multiple endocrine neoplasia (MEN) type 2 syndromes. In MEN2A, Codon 634 in exon 11 is the most commonly altered codon. V109G polymorphism is associated with sporadic MTCs negative for RET mutations, and might influence the clinical course of the patients affected by MTC. Interesting results come from two large phase III clinical trials with two targeted tyrosine kinase inhibitors (TKIs), vandetanib and cabozantinib.